Patient Perspectives on Blended Internet-Based and Face-to-Face Cognitive Behavioral Therapy for Alcohol Use Disorder: Qualitative Study - Kristine Tarp; Regina Christiansen; Randi Bilberg; Simone Borkner; Caroline Dalsgaard; Marie Paldam Folker; Anette Søgaard Nielsen (JMIR Publications, 2024)
BackgroundHarmful alcohol consumption has been identified as a major contributor to disease, mortality, and social harm, accounting for 5.3% of worldwide deaths annually. In Denmark, an estimated 150,000 people suffer from alcohol use disorder (AUD), but a low proportion seek treatment due to person- and treatment-related barriers. Internet-based cognitive behavioral therapy (iCBT) has shown positive effects on the treatment gap, with patients reporting benefits such as increased knowledge and flexibility. However, there is a lack of research on blended cognitive behavioral therapy (bCBT), which combines face-to-face CBT (FtF CBT) and iCBT for AUD. ObjectiveThis study aims to investigate user experiences of bCBT. More specifically, it seeks to explore the advantages and disadvantages that users have experienced with bCBT for AUD, as well as their motivations for choosing this treatment format. MethodsA total of 30 patients who had participated in the Blend-A (Blending Internet Treatment into Conventional Face-to-Face Treatment for AUD) study and received the intervention were contacted and offered the opportunity to participate in semistructured individual telephone interviews. Of these, 12 patients consented to participate. Furthermore, an additional participant was approached at a municipal clinic and agreed to engage in an individual FtF interview. Thus, the final sample consisted of 13 patients. The interviews explored their background, experiences with digital technology, motivations for choosing internet-based treatment, and experiences with the program during AUD treatment. The interviews were audio-recorded and transcribed in full length and analyzed using thematic analysis. All data were anonymized and securely stored. ResultsWe found that users experienced several advantages of iCBT over a larger part of the treatment course, including increased anonymity and privacy. Most importantly, it offered flexibility, allowing patients to focus on their rehabilitation process at their own pace. Patients appreciated the availability of written text in the online program, finding it helpful for gaining knowledge and understanding of AUD and its impact on the individual with the condition. They emphasized how the assignments helped them fully engage in treatment by first acknowledging their problem with alcohol and then dedicating time to self-reflection before FtF sessions, allowing for more in-depth discussions with the therapist. They also appreciated the reminders, which motivated them to complete their assignments. ConclusionsOverall, patients perceived more benefits than disadvantages in using bCBT. Essentially, bCBT offers a form of assisted autonomy that cannot be fully achieved through iCBT or FtF CBT alone. It is only through their combination that patients can fully appreciate the benefits of the treatment, as they have time for self-reflection, with guidance from the therapist between FtF CBT sessions. Trial RegistrationClinicalTrials.gov NCT04535258; https://clinicaltrials.gov/ct2/show/NCT04535258